Formation and transport of corrosive water in the Pacific Arctic region. (June 2018) - Cross, Jessica N.; Mathis, Jeremy T.; Pickart, Robert S.; Bates, Nicholas R.
Abstract: Ocean acidification (OA), driven by rising anthropogenic carbon dioxide (CO2 ), is rapidly advancing in the Pacific Arctic Region (PAR), producing conditions newly corrosive to biologically important carbonate minerals like aragonite. Naturally short linkages across the PAR food web mean that species-specific acidification stress can be rapidly transmitted across multiple trophic levels, resulting in widespread impacts. Therefore, it is critical to understand the formation, transport, and persistence of acidified conditions in the PAR in order to better understand and project potential impacts to this delicately balanced ecosystem. Here, we synthesize data from process studies across the PAR to show the formation of corrosive conditions in colder, denser winter-modified Pacific waters over shallow shelves, resulting from the combination of seasonal terrestrial and marine organic matter respiration with anthropogenic CO2 . When these waters are subsequently transported off the shelf, they acidify the Pacific halocline. We estimate that Barrow Canyon outflow delivers ~2.24 Tg C yr -1 to the Arctic Ocean through corrosive winter water transport. This synthesis also allows the combination of spatial data with temporal data to show the persistence of these conditions in halocline waters. For example, one study in this synthesis indicated that 0.5–1.7 Tg C yr -1 may be returned to the atmosphere via air-sea gas exchange of CO2 during upwelling events along the Beaufort Sea shelf that bring Pacific halocline waters to the ocean surface. The loss of CO2 during these events is more than sufficient to eliminate corrosive conditions in the upwelled Pacific halocline waters. However, corresponding moored and discrete data records indicate that potentially corrosive Pacific waters are present in the Beaufort shelfbreak jet during 80% of the year, indicating that the persistence of acidified waters in the Pacific halocline far outweighs any seasonal mitigation from upwelling. Across the datasets in this large-scale synthesis, we estimate that the persistent corrosivity of the Pacific halocline is a recent phenomenon that appeared between 1975 and 1985. Over that short time, these potentially corrosive waters originating over the continental shelves have been observed as far as the entrances to Amundsen Gulf and M'Clure Strait in the Canadian Arctic Archipelago. The formation and transport of corrosive waters on the Pacific Arctic shelves may have widespread impact on the Arctic biogeochemical system and food web reaching all the way to the North Atlantic.